(untitled) (Research, Society and Development, 2021)
Introduction: Cardiovascular diseases, such as acute myocardial infarction (AMI), are one of the main causes of death in Brazil and worldwide, affecting approximately 183 per 100,000 inhabitants. It becomes important to control blood pressure, and especially dyslipidemia observed in most patients through diets. Objectives: to evaluate the effects of linoleic acid in the prevention of acute myocardial infarction. Methodology: This is a comprehensive literature review that rigorously reviews and combines research using different methods. To select the studies, a thorough reading of the titles and abstracts was performed, in order to verify which ones fit the guiding question and the inclusion and exclusion criteria. Results and discussion: Linoleic acid is a precursor of arachidonic acid, which participates in the synthesis of biologically active mediators, such as prostaglandins, thromboxanes and leukotrienes. These substances act as inflammatory, stimulant and healing mediators. Patients with acute myocardial infarction (AMI) may benefit from polyunsaturated fatty acid supplementation. Conclusion: The intake of fatty acids is related to a decrease in the risk of cardiac arrest, having a regulatory effect on the electrical properties of the myocardium, reducing ventricular arrhythmias and the risk of sudden death.